STUDI KUALITAS PERMUKAAN PEMBUBUTAN KERING PADA BAJA AISI 4340 MENGGUNAKAN PAHAT PVD DAN CVD BERLAPIS - Junaidi Junaidi; Yulfitra Yulfitra (Jurnal Simetri Rekayasa, 2021)
In order to manufacture a component of high quality, surface quality is the most important requirement for users. An understanding of the chip removal process in metal cutting is essential for material selection and tool design, and also for ensuring consistent dimensional accuracy and surface integrity of the finished product. Friction in metal cutting affects cutting power, machining quality, tool life and production costs. The most important measure of surface quality during the machining process is the average surface roughness (Ra). When the tool wear reaches a certain value, the cutting force, vibration and cutting temperature increase, causing the dimensional error to be larger than the tolerance and the surface integrity to deteriorate. This tool wear is one of the most important aspects of hard turning. Usually abrasion, adhesion and diffusion are considered the main tool wear mechanisms in hard machining. However, the individual effect of each mechanism depends on the tool geometry, tool grade or class, cutting parameters, and workpiece hardness. Tool wear increases linearly with increasing cutting parameters. This indicates that the increased tool wear at higher cutting conditions may be due to abrasion especially at the rake and flank during machining. The selection of dry machining is carried out with environmental efforts to minimize or eliminate the use of cutting fluid waste.